Efficacy of Nigella sativa oil to relieve effects of the lead monoxide toxicity on testicular efficiency and sexual behaviour disorders in albino rats - Chabuk, Halla Abdul-Hadi; Awadh, Sura Abdalkahalek (Penerbit Universiti Kebangsaan Malaysia, 2022)
The prevalence of testicular toxicity induced via contamination with heavy metals is increasing worldwide, and a close connection between testicular toxicity and lead has recently been identified. The present study demonstrated the possible therapeutic and protection properties of Nigella sativa oil (NSO) against dangerous testicular toxicity and sexual behaviour disorders in rat models induced by lead monoxide (PbO) food poisoning. A total of 24 male rats were used and divided into four groups, consisting of Group 1: Control (1 mL of distilled water); Group 2: PbO (80 mg/kg); Group 3: NSO (0.5 mL/rat); and Group 4: (NSO+PbO) 0.5 mL/rat of NSO, followed by PbO (80 mg/kg/day) respectively for 60 days. The testosterone, follicle-stimulating hormone (FSH), luteinizing hormone (LH), 17 beta-hydroxysteroid dehydrogenase activity (17β-HSD), sperm parameters, and sexual behaviour (copulation behaviour test) were measured. The results showed that sex hormone levels were significantly decreased (p<0.05) in rats exposed to PbO, while the levels of these hormones were significantly higher in rats exposed to NSO and NSO+PbO. The sperm parameters (numbers, concentrations, motilities, and abnormality) were lower in rats exposed to PbO compared to those in the control, NSO, and NSO+PbO groups that showed significant increases. Sperm abnormality and 17β-HSD activity showed a significant increase at p<0.05 in the group exposed to the PbO compared to those of the control, NSO, and NSO+PbO groups. The results also significantly suppressed sexual behaviour in rats exposed to PbO compared to those in the control, NSO, and NSO+PbO groups, rats were administered NSO+PbO showed improvement in sexual behaviour parameters compared to PbO groups. PbO toxicity was obvious in the reproductive tract through severe histopathological changes. The impact of lead on tissues was partially mitigated by NSO. The study showed protective effects of N. sativa oil against changes in sex hormones, sperm characteristics, and sexual behaviour in male rats exposed to lead monoxide-induced testicular toxicity.